Mood and Modality in Interpersonal Meaning of Joseph Robinette Biden Victory Speech - Panggabean, Devi Sari; Sinar, T. Silvana; Nurlela (Indonesian Journal of Educational Research and Review, 2023)
Speech involves the articulation of one's ideas and emotions. Politicians must possess the skill to effectively utilize language. Prior research underscores the significance of studying the political language, as it empowers individuals to grasp how those aspiring to attain, wield, and retain authority employ language. The purpose of this study is to analyze how mood and modality were used in the victory speech. This research applies qualitative design. The transcription of Joe Biden's victory speech is the subject of this investigation. Mr. Biden convey commitments and responsibility connected with the program that he will run; however, we don't know whether it will be run or no. This research applied qualitative research. The analysis is using data collection, data reduction, data display, and conclusion. According to the findings of this study, there are three distinct categories: value, modality, and mood. Declarative mood is the most common type; 193 clauses, or about 94%, are in the imperative mood, followed by seven clauses, or 3,4%, and three clauses, or about 1,5 percent, in the interrogative mood. The dominant modality value is median, there are eighteen provisions or around 62,1%, then, at that point, trailed by eight clauses or around 27,6% as low worth and the latter is three conditions or 10,3% for high worth. The dominant type of modality is obligation. Eleven clauses, or approximately 37.9 percent, are classified as obligation, ten clauses, or approximately 34.5%, as probability, and eight clauses, or approximately 26.7 percent, as inclination.